PAR2 expression in peripheral blood monocytes of patients with rheumatoid arthritis. Issue 6 (30th January 2012) - Crilly, A; Burns, E; Nickdel, M B; Lockhart, J C; Perry, M E; Ferrell, P W; Baxter, D; Dale, J; Dunning, L; Wilson, H; Nijjar, J S; Gracie, J A; et al.
Abstract : Objectives: Proteinase-activated receptor 2 (PAR2 ) is a G protein-coupled receptor activated by serine proteinases with proinflammatory activity. A study was undertaken to investigate the presence and functio©nal significance of PAR2 expression on rheumatoid arthritis (RA)-derived leucocyte subsets. Methods: Venous blood was obtained from patients with RA and osteoarthritis (OA) as well as healthy control subjects. Surface expression of PAR2 on peripheral blood mononuclear cells (PBMCs) was analysed by flow cytometry and interleukin 6 (IL-6) generation by ELISA. Results: Patients with RA had elevated but variable surface expression of PAR2 on CD14+ monocytes compared with control subjects (median (1st to 3rd quartiles) 1.76% (0.86–4.10%) vs 0.06% (0.03–0.81%), p<0.0001). CD3+ T cells showed a similar pattern with significantly higher PAR2 expression in patients with RA compared with controls (3.05% (0.36–11.82%) vs 0.08% (0.02–0.28%), p<0.0001). For both subsets, PAR2 expression was significantly higher (p<0.00001) in patients with high levels of disease activity: PAR2 expression for both CD14+ and CD3+ cells correlated to C reactive protein and erythrocyte sedimentation rate. Furthermore, in a cohort of patients with newly diagnosed RA, elevated PAR2 expression in both CD14+ and CD3+ cells was significantly reduced 3 months after methotrexate or sulfasalazine treatment and this reduction correlated significantly with the reduction in the 28-joint Disease Activity Scale score (p<0.05). PAR2 expression on cells from patients with OA was low, similar to levels seen in control subjects. Generation of IL-6 by monocytes in response to a selective PAR2 agonist was significantly greater in patients with RA than in patients with OA and control subjects (p<0.05). Conclusions: These findings are consistent with a pathogenic role for PAR2 in RA.